2D Materials: Resistive Switching Performance Improvement via Modulating Nanoscale Conductive Filament, Involving the Application of Two‐Dimensional Layered Materials (Small 35/2017). Issue 35 (14th September 2017) - Li, Yu; Long, Shibing; Liu, Qi; Lv, Hangbing; Liu, Ming
Abstract : In article number1604306, Shibing Long, Ming Liu and co‐workers, review performance improvements in resistive switching devices. The main focus is on filamentary switching behavior, in the aspects of materials modulation, device structure design and switching operation scheme optimization. In particular, 2D nanomaterials that play active roles and exhibit prominent effects in applications are discussed.